Hikmah as a Solution to the Crisis of Adab in Buya Hamka’s Thought - Islam, Muhammad Thoriqul; Nasution, Alhafidh; Al Baqi , Safiruddin; Novitasari, Dwiana; Ikmah, Amit Dana; Azmi, M.Ulul; Oktaviani, Ida Nur (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2025)
This research aims to analyze Buya Hamka’s perspective on resolving the crisis of adab (ethics) through the Qur’anic concept of hikmah. Employing a qualitative library research method, the study uses thematic content analysis to examine primary sources, particularly Hamka’s Tafsir al-Azhar, essays, and speeches, alongside relevant secondary literature. The analysis is structured through three stages: comparing various interpretations of hikmah and adab across Hamka’s works, contrasting differing emphases in context, and criticizing through a thematic coding framework that includes hikmah, adab, qalb, ‘aql, and iman. This approach enables the study to extract deeper meanings and reveal the interconnectivity of Hamka’s ethical thought. The results show that hikmah is the harmony of interconnected meanings, where the achievement of hikmah is the main goal for those who study it. Hamka proposed several ways to gain hikmah: reading and understanding the Qur'an, thinking deeply, and imitating good behavior. Hamka argues that hikmah can be a solution to overcoming the crisis of adab through strengthening the seven aspects of spiritual intelligence, namely al-ruh, al-qalb, al-nafs, al-aql, faith, worship, and adab. Spiritual intelligence has an important role in maintaining mental health, ultimately contributing to civilized individuals' formation. This study contributes to the field of Islamic thought and Living Qur’an by offering a Qur’anic-rooted philosophical framework of hikmah through the lens of Buya Hamka’s scholarship, promoting an integration between inner ethics (adab) and outer conduct in contemporary Muslim life.